PERCOBAAN PEMBUATAN PERNIS DARI KOPAL ASAL PROBOLINGGO - Totok K; Waluyo Waluyo; Erik Dalian; Enen Edriana (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
Varnish is a particular liquid-phase substance composed of resin oil, solvent, pigments, drying agent, and other additive matters; and when it is applied to surface of a body, it will develop to a dry, hard, and sticky layer.Copal is one of the Indonesian export commodities that places 80-percent share in world market. In Indonesian, one of the potential regions as the origin and source of copal is Probolinggo in East Java. In an attempt to use copal domesticall an experiment of varnish making was conducted using prime quality copal (UT) obtained from Probolinggo. The solvents used were a mixture of propanol-2 and ethyl acetat at a ratio 1 : 2, added with 0.3% dry cobalt, 0.9% dry calcium, and 18% synthetic alkyd. The quality of varnish was eventually assessed. The chemical were also previously used for varnish making with the copal abtained from Sukabumi (West Java). The quality of copal produced was comparable to those of commercial varnish, and met with the ICl standard. An experiment with copal from Probolinggo was also conducted. The results revealed that the quality of varnish was still lower than the commercial varnish, and did not meet the ICl standard, especially in drying duration, touching sense, shearing strength and evenness in brushing. This was possibly caused by the high viscosity of the varnish (i.e 7.5 centipoise) exceeding the standard (6 - 7 centipoise).